The State and Poverty Alleviation in Advanced Capitalist Democracies - Stephanie Moller; David Bradley; Evelyne Huber; François Nielsen; John D. Stephens (Luxembourg Income Study (LIS), 2001)
We analyze the impact of the state on the incidence of poverty in the working-age population of 14 advanced capitalist democracies between 1970 and 1997 using an unbalanced panel design. We utilize poverty measures based on micro-level data from the Luxembourg Income Study in conjunction with pooled time series data from the Huber, Ragin and Stephens (1997) database. We argue that economic factors including de-industrialization and unemployment largely explain pre-tax, pre-transfer poverty rates of the working age population in advanced capitalist states. These rates, however, are theoretical as advanced democracies redistribute resources through taxes and transfers. We show that the extent of redistribution (measured as poverty reduction via taxes and transfers) is explained directly by welfare state generosity as well as constitutional structure (number of veto points) and the strength of the left, both in unions and in government.
Keywords: 330; Armut; Armutsbekämpfung; Einkommensumverteilung; Sozialpolitik; EU-Staaten; Norwegen; Schweiz; Australien; Kanada; USA